Benefits of the kangaroo method for low birth weight newborns (Research, Society and Development, 2023)
This study aims to describe the benefits of the kangaroo method for low birth weight newborns. This is an integrative literature review, carried out in the Medical Literature (MEDLINE), Latin American and Caribbean Literature in Health Sciences (LILACS) and Nursing Database (BDENF) databases, via the Virtual Health Library with health descriptors that included publications from 2016 to 2020. The final sample consisted of 11 articles, being refined from an exhaustive reading. In the analysis of the implementation process of the kangaroo method and the humanized care for low birth weight newborns, the researched literature shows that with the changes made in the health networks, the method has been showing several benefits such as: better recovery and shorter hospitalization time , reduction of mortality and infections, low cost in addition to favoring bonding, improvement of hemodynamic stability and physical growth, reduction of stressors, among others. The kangaroo method provides numerous benefits, offering humanized strategies in the treatment of low birth weight newborns, contributing to a good therapeutic evolution. Thus, it is necessary to encourage this intervention with the health team.